Design and rationale for the "Me & My Heart" (eMocial) study: A randomized evaluation of a new smartphone‐based support tool to increase therapy adherence of patients with acute coronary syndrome. Issue 11 (6th September 2019) - Krackhardt, Florian; Maier, Lars S.; Appel, Karl‐Friedrich; Köhler, Till; Ghanem, Alexander; Tschoepe, Carsten; Dahl, Jürgen vom; Degenhardt, Ralf; Niklasson, Anna; Ahlqvist, Matti; Waliszewski, Matthias W.; Jörnten‐Karlsson, Magnus
Abstract: A novel smartphone‐based patient support tool was developed to increase the adherence to antiplatelet therapy and lifestyle changes in patients after coronary angioplasty for acute coronary syndrome (ACS). The eMocial study (ClinicalTrials.gov Identifier: NCT02615704) investigates whether an electronic support tool will improve adherence to comedication and lifestyle changes in ACS patients. The primary hypothesis of this trial is that an electronic support tool can increase adherence to comedication (primary endpoint) thereby supporting positive lifestyle changes (secondary endpoints). Patients hospitalized with ACS (ST elevation myocardial infarction [STEMI], non‐ST elevation myocardial infarction [NSTEMI], or unstable angina pectoris) and treated with ticagrelor coadministered with low‐dose acetylsalicylic acid will be randomized 1:1 to an active group receiving the patient support tool via a smartphone‐based application or to a control group without the patient support tool. Patient questionnaires to evaluate lifestyle changes and quality of life will be used at baseline and at the end of the 48‐week observation phase. Patients are asked to fill out questionnaires to determine their adherence, treatment attitudes, health‐care utilization and risk factors on a monthly basis. The study was started in February 2016 and the completion date is scheduled for October 2019. For final analysis 664 patients are expected be available. Preliminary baseline demographics were unstable angina pectoris (13.7%), NSTEMI (49.9%), STEMI (36.4%), male gender (86.3%), and diabetes mellitus (17.6%). Our study could significantly help to understand how inadequate adherence to antiplatelet therapy in ACS patients could be improved with a smartphone‐based application.